Effect of Functional Groups and pH on the Affinity and Adsorption Capacity of Activated Carbon: Comparison of Homogeneous and Binary Langmuir Model Parameters - Sirous Nouri (Adsorption Science & Technology)
The adsorption of p -nitrophenol (an electrolyte) and nitrobenzene (a non-electrolyte) on activated carbon was carried out at 301 K under controlled pH conditions. The experimental isotherms were fitted to the homogeneous Langmuir model and the binary Langmuir model. Variation of the model parameters with solution pH was studied. The fitted parameters obtained from the Langmuir equations (homogeneous and binary models) showed that both the maximum amount of solute adsorbed (Q max ) and the adsorption affinity of the carbon (K 1 ) towards the electrolytic adsorbate exhibited the more significant decrease. Under pH conditions below the pK a value of p -nitrophenol (when the adsorbate existed in a molecular form), both the solubility of the adsorbate and the electron density of its aromatic ring were significant factors affected the extent of London dispersion interactions. At higher solution pH values, electrostatic forces had a significant impact on the extent of adsorption. The influence of pH must be considered in terms of its combined effect on the carbon surface and on the solute molecules. It was confirmed that the uptake of the molecular forms of the aromatic solutes was dependent on the substituents attached to the aromatic ring. The adsorption of p -nitrophenol at higher pH values depended on the concentration of the anionic form of the solute present in the aqueous solution.